Heart-Focused Anxiety Affects Behavioral Cardiac Risk Factors and Quality of Life: A Follow-Up Study Using a Psycho-Cardiological Rehabilitation Concept - Schmitz, Christoph; Wedegärtner, Sonja Maria; Langheim, Eike; Kleinschmidt, Judit; Köllner, Volker (Frontiers in Psychiatry, 2022)
BACKGROUND: Heart-focused anxiety (HFA) raises the risk for adverse outcomes in patients with heart disease. Despite this great importance, it is rarely assessed in clinical practice. Three dimensions are commonly defined in the context of HFA: heart-related fear, avoidance, and attention. The impact of these aspects on cardiac risk factors is essentially unclear. In this study, we investigated the relationship between HFA and behavioral cardiac risk factors as well as health-related quality of life (HRQoL), which represent important treatment outcomes of inpatient psycho-cardiological rehabilitation. METHODS: A prospective observational design was used to examine 238 rehabilitation inpatients with comorbidity of cardiac disease and psychiatric disorder. We assessed HFA using the Cardiac Anxiety Questionnaire (CAQ), HRQoL using the SF-12 Health Survey, exercise capacity using the 6-minute walk test, and smoking behavior, respectively at admission (t0) and discharge (t1). Physical activity was assessed at t0 and in a follow-up survey 6 months after discharge (t2) using the International Physical Activity Questionnaire (IPAQ). Multiple regression models were used to analyze the predictive value of HFA for the outcome variables at t0, t1, and t2, adjusted for socio-demographic factors and depression. Predictive values for changes over time were evaluated by the regressor variable approach. RESULTS: Exercise capacity and physical activity were negatively predicted by baseline heart-related avoidance, both cross-sectionally and prospectively. Avoidance at t1 also negatively predicted long-term changes over time in physical activity at t2. Total HFA and the subcomponent avoidance negatively predicted physical HRQoL both cross-sectionally and prospectively. Mental HRQoL was cross-sectionally predicted by heart-focused attention at t0, and prospectively predicted by total HFA and by avoidance. Regarding changes in the course of rehabilitation, baseline avoidance negatively predicted improvement in physical HRQoL during rehabilitation. Concerning smoking behavior, no associations with HFA were found. CONCLUSIONS: HFA is a relevant inhibiting factor for the achievement of therapy goals in psycho-cardiological rehabilitation such as health behavior and HRQoL. Heart-related avoidance in particular, has a negative impact on exercise capacity, physical activity, and self-reported physical health. Its prospective negative predictive value for physical activity and physical health underlines the relevance of HFA for psycho-cardiological interventions.